Eles não usam black-tie: uma leitura das micro-relações de poder em cena - Cavalcante, Ana Rachel da Silva (2017)
This research is focused in the analysis of the micro-relations of power consisted between characters in the play Eles Não Usam Black-Tie, written by Gianfrancesco Guarnieri, in 1955. In this context, we will present a scenic experiment which represents the micropower inside the scene. The methodology used in this study was based on the reading of the Guarnieri’s play and making observations about the inter-relationship between the characters. This observation is made from the perspective of power. To support our analyses, we used the set of placements showed by the French writer Michel Foucault, especially in his work Microfisica do Poder which presents the influences of the power. We used the reflexions obtained by Sábato Magaldi, Décio de Almeida Prado, Edelcio Mostaço and Anatol Rosenfeld to understand the dramatic aspects and the macro-political structure of the time where the play was written. Thus, this research aims to make an easier understanding of the perception of micro-relations present in Eles Não Usam Black-Tie and show a possible visualization of these elements inside the scene. In this respect, we used the reflexions obtained in works from authors as: Patrice Pavis, Josette Féral, Naira Ciotti, Roberto Machado e Gilles Deleuze.